Rarefaction Effects in Hypersonic Wind Tunnel in Shock Wave Boundary Layer Interaction Phenomena - Votta, Raffaele; Ranuzzi, Giuliano; Clemente, Marco Di; Schettino, Antonio; Marini, Marco (IntechOpen, 2011)
None